Fast determination of multi-mycotoxins in corn by dispersive solid-phase extraction coupled with ultra-performance liquid chromatography with tandem quadrupole time-of-flight mass spectrometry - Yan WANG; Yan-jie DONG; Zeng-mei LI; Li-gang DENG; Chang-ying GUO; Shu-qiu ZHANG; Da-peng LI; Shan-cang ZHAO (Journal of Integrative Agriculture, 2016)
A fast analytical method for the simultaneous determination of 9 mycotoxins, including aflatoxins (B1, B2, G1, and G2), fumonisins (B1, B2 and B3), zearalenone, and deoxynivalenol in corn using dispersive solid-phase extraction method and ultra-performance liquid chromatography coupled to tandem quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) was developed and validated. Samples were extracted with acetonitrile-water (84:16, v:v, containing 1% acetic acid) using ultrasonic extraction. The extracts were purified with a dispersive SPE method using C18 as a cleaning agent. The final clear extracts were dried by nitrogen blowing and subsequently redissolved in methanol-water (5:5, v:v). The samples were then analyzed by UPLC-Q-TOF-MS with 0.1% formic acid in ammonium acetate-methanol as mobile phase. The mean recoveries were ranged from 68.0 to 120.0%, and the relative standard deviation (RSD) ranged from 0.18 to 6.29%. Limits of detections ranged from 0.05 to 50 μg kg−1, and limits of quantification ranged from 0.1 to 200 μg kg−1, which were below the legal limits set by the European Union for the legislated mycotoxins. The developed method was applied to 130 corn samples. Among the mycotoxins studied, aflatoxins B1 and fumonisins B1, B2 and B3 were the most predominant mycotoxins, and their concentrations were 0–593.12, 0–2.01×104, 0–6.94×103 and 0–3.05×103 μg kg−1, respectively.